Transcriptomic profiling of a facultative symbiotic white gorgonian provides insights into symbiosis regulation in octocorals - Judith Camps-Castellà; Patricia Prado; Xavier Salvador; Gert Wörheide; Miquel Pontes; Sergio Vargas (Coral Reefs, 2026)
Symbiotic relationships play important physiological roles in cnidarians; however, the molecular mechanisms underlying their establishment and regulation have only been elucidated in model systems, like the anemone Exaiptasia sp., while remaining largely unexplored in other cnidarian groups, including gorgonians. In this study, we investigate the transcriptional changes associated with facultative symbiosis in the white gorgonian, Eunicella singularis , a species that occurs in a non-symbiotic state in caves and deeper waters, while occurring in a symbiotic state in shallow or light-exposed habitats. We identified nearly 3000 differentially expressed genes (DEGs) between symbiotic and non-symbiotic colonies. Gene co-expression network analysis identified six significant metamodules, accounting for 62% of the transcripts, and pointing to key functional differences between both symbiotic states. Gene Ontology (GO) enrichment analyses showed that genes upregulated in symbiotic colonies were enriched in glial cell development, epidermal growth factor signaling, and cellular stress responses, suggesting enhanced cellular proliferation and protection mechanisms. In contrast, non-symbiotic colonies showed enrichment in pathways related to cellular communication, response to abiotic stress, and metabolic regulation. In total, 134 transcripts were identified as homologous to Exaiptasia sp. symbiosis-associated genes, and several genes upregulated in Eunicella were also linked to the transport of photosynthetically fixed carbon and the facilitated glucose transporter (GLUT8) in symbiotic colonies. Our results provide valuable insights into the molecular mechanisms underlying symbiosis in octocorals. Furthermore, the identification of conserved symbiosis-related genes across cnidarians suggests that common genetic pathways might be involved in maintaining symbiosis with dinoflagellates.

Revisiting Chilean gorgonians (Cnidaria: Octocorallia: Gorgoniidae): taxonomic clarification and molecular phylogeny of Leptogorgia chilensis and Phycogorgia fucata - Judith Camps-Castellà; Sergio Vargas; Iván Vera-Escalona; Patricia Prado; Iván A. Hinojosa; Antonio Brante (Systematics and Biodiversity, 2025)

Trophic role and predatory interactions between the blue crab, Callinectes sapidus, and native species in open waters of the Ebro Delta - Patricia Prado; Marc Baeta; Estel Mestre; Marco Antonio Solis; Ignasi Sanhauja; Ignasi Gairin; Judith Camps-Castellà; Silvia Falco; Manuel Ballesteros (Estuarine, Coastal and Shelf Science, 2024)

Structural attributes and macrofaunal assemblages associated with rose gorgonian gardens (Leptogorgia sp. nov.) in Central Chile: opening the door for conservation actions - Judith Camps-Castellà; Patricia Prado; José Tena-Medialdea; Antonio Brante; Iván A. Hinojosa (Coral Reefs, 2024)
Gorgonians (like corals) are important habitat-forming organisms that support a diversity of macrofauna. This study explored structural attributes of gorgonian gardens formed by rose gorgonians ( Leptogorgia sp. nov.) and associated macrofaunal assemblages in Caleta Pichicuy (Central Chile). Hierarchical sampling was conducted at 20 m depth (maximum colony abundances) in order to assess spatial variability in abundance and colony attributes at two spatial scales (among sites and rocky walls). The abundance and composition of the associated vagile and sessile macrofauna were also examined using univariant (Taxa richness and Shannon index ( H’e )) and multivariant approaches and were compared with adjacent bare rocky habitats. Our results showed a high abundance of gorgonians (ca. 28.9–36.5 colonies m −2 ) compared to other gorgonian gardens in the world. For structural attributes, our results showed smaller colonies with thicker holdfasts in more exposed sites, suggesting the influence of hydrodynamic forces on the colony morphology. Taxa richness and H’e of vagile fauna showed threefold and twofold, respectively, higher values in gorgonian gardens compared to bare walls, but no differences were observed for sessile fauna. In addition, PCoA and PERMANOVA evidenced a distinctive assemblages’ composition between habitats for both vagile and sessile fauna. Correlation analyzes and dbRDA showed, however, little association between structural attributes and associated faunal assemblages ( R 2 = 0.06, and ca. 3–9.4% of the total variation explained, respectively). Our results constitute the first assessment of structural habitat complexity and accompanying fauna in these gorgonian gardens and establish the baseline for understanding possible future changes associated to human activities.

High temporal resolution of hydrogen peroxide (H2O2) dynamics during heat stress does not support a causative role in coral bleaching - Marlen Schlotheuber; Christian R. Voolstra; Dirk de Beer; Emma F. Camp; Judith M. Klatt; Mattia Ghilardi; Katharina Neumüller; Sara Ousley; Sonia Bejarano (Coral Reefs, 2024)
Human-induced climate change is causing ocean warming that triggers the breakdown of the coral–algal symbiosis. The proximate cause of this phenomenon, known as coral bleaching, is commonly attributed to the overproduction of reactive oxygen species (ROS) by the thermally stressed photosynthetic algal symbionts. However, direct evidence that algal ROS production (e.g., in the form of H 2 O 2 ) and coral physiological stress are the ultimate cause of bleaching remains ambiguous. Here, we investigated the temporal dynamics of H 2 O 2 and oxygen (O 2 ) concentrations during thermally induced coral bleaching to disentangle cause from consequence. Microsensors at the tissue interface of Pocillopora damicornis measured H 2 O 2 and O 2 concentrations while exposing single nubbins to baseline temperatures (30 °C) and to minor (33 °C), moderate (36 °C), and high (39 °C) levels of acute heat stress using the Coral Bleaching Automated Stress System (CBASS). We show that a temporary decline in O 2 concentration, accompanied by a declining photosynthetic efficiency and loss of Symbiodiniaceae and pigmentation, is the initial response to moderate thermal stress. This response was neither provoked nor followed by an increased H 2 O 2 concentration at the coral tissue interface. A steady light-independent increase of H 2 O 2 was only detected during high heat stress, resulting in the complete and permanent loss of photosynthetic activity. Our findings do not support a direct connection between algal photodamage and an increase in H 2 O 2 concentration during thermally induced bleaching and suggest that more research on the function of H 2 O 2 is warranted. This notion is further substantiated by the observation of an additional source of H 2 O 2 , likely oxidative bursts, that were common at the baseline temperature and under minor heat stress, while their occurrence decreased at moderate and high heat stress. Resolving the multifaceted and dynamic roles of H 2 O 2 in coral bleaching is critical to better understand the response of the coral holobiont to thermal stress and identifying the processes underlying the breakdown of the coral–algal symbiosis.

Evaluating the extent and impact of the extreme Storm Gloria on Posidonia oceanica seagrass meadows - Candela Marco-Méndez; Núria Marbà; Ángel Amores; Javier Romero; Mario Minguito-Frutos; María García; Jordi F. Pagès; Patricia Prado; Jordi Boada; José Luis Sánchez-Lizaso; Juan Manuel Ruiz; Gregori Muñoz-Ramos; et al. (Science of The Total Environment, 2024)

Usefulness of intraoperative bile culture in patients with acute calculous cholecystitis with previous biliary events: does the postoperative management change? - Melissa Arias-Avilés; Jaume Tur-Martínez; Judith Camps-Lasa; Èric Herrero-Fonollosa; María Isabel García-Domingo; Esteban Cugat-Andorrà (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Taxonomic status and geographic distribution of Phycogorgia fucata (Valenciennes 1846) (Octocorallia: Gorgoniidae) - Odalisca Breedy; Judith Camps-Castellà; G. Försterra; Verena Häussermann (Marine Biology Research, 2021)

Trophic plasticity in P. lividus: herbivory, detritivory and omnivory as a function of resource availability - Judith Camps; Javier Romero; Patricia Prado (Frontiers in Marine Science, 2019)

New Mediterranean Biodiversity Records (November 2018) - MEHMET BAKİ YOKEŞ; VASILIS ANDREOU; RIGERS BAKIU; SARA BONANOMI; JUDITH CAMPS; GEORGE CHRISTIDIS; FABIO CROCETTA; IOANNIS GIOVOS; ANDREA GORI; TEA JURETIĆ; SELAHATTİN ÜNSAL KARHAN; STELIOS KATSANEVAKIS; et al. (Mediterranean Marine Science, 2018)